2003
DOI: 10.1161/01.cir.0000087602.91755.19
|View full text |Cite
|
Sign up to set email alerts
|

Phase I Drug and Light Dose-Escalation Trial of Motexafin Lutetium and Far Red Light Activation (Phototherapy) in Subjects With Coronary Artery Disease Undergoing Percutaneous Coronary Intervention and Stent Deployment

Abstract: This study demonstrates that coronary MLu PT seems safe, and the maximum well-tolerated MLu dose and range of tolerated light doses were identified. These data can be used in phase II efficacy trials of MLu PT for the treatment of coronary atherosclerosis or vulnerable plaque.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
64
0
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(67 citation statements)
references
References 27 publications
1
64
0
2
Order By: Relevance
“…Clinical use of PDT therapy has been limited to nonrandomized, nonplacebo-controlled trials, with red light activation of 5-aminolaevulinic acid at 630 nm or motexafin lutetium at 730 nm (35)(36)(37)(38). Although motexafin lutetium is well tolerated at lower doses, at higher doses a significant number of patients had paraesthesia (38).…”
Section: Discussionmentioning
confidence: 99%
“…Clinical use of PDT therapy has been limited to nonrandomized, nonplacebo-controlled trials, with red light activation of 5-aminolaevulinic acid at 630 nm or motexafin lutetium at 730 nm (35)(36)(37)(38). Although motexafin lutetium is well tolerated at lower doses, at higher doses a significant number of patients had paraesthesia (38).…”
Section: Discussionmentioning
confidence: 99%
“…The same agent has been administered to patients undergoing coronary stenting in a safety study and found to be well tolerated. 222 Using a different photodynamic agent, Waksman et al 223 demonstrated that photodynamic therapy can reduce neointimal growth without suppressing reendothelialization of a stent in a porcine model. These early results suggest that photodynamic therapy might eventually have a role in the local or regional treatment of vulnerability.…”
Section: Photodynamic Therapy For Vulnerable Coronary Arteries and Plmentioning
confidence: 99%
“…Tests capable of screening a large population to determine patients that require more detailed intracoronary evaluation must be developed. Local treatment strategies have been proposed, including lesion stabilization with drug-eluting stents 88,89 and photodynamic therapy, 90,91 but the long-term clinical viability of these approaches is currently unknown. While there is still much to be done, we anticipate that the unique capabilities of OCT as an investigational tool for high-risk lesions will serve the cardiology community well as it advances to understand, identify, and ultimately treat the vulnerable plaque.…”
Section: Resultsmentioning
confidence: 99%